Pengaruh Media Tanam dan Pemanfaatan Pupuk Organik Cair dari Air Cucian Beras terhadap Pertumbuhan Tanaman Seledri (Apium graveolus L.) - Andi Herwati; Nur Haenir; Haerul - (Jurnal Agrotan, 2023)
Celery is commonly used as a food mixture as a flavor enhancer and can also be used as a medicinal plant. In order to meet public demand, it is necessary to increase the production of celery plants, one of which can be increased by using planting media to fulfill the appropriate nutrients. The purpose of this study was to determine the effect of planting media and liquid organic fertilizer from rice washing water which had the best effect on celery plants. This research was conducted from January to April 2022 at Samangki Village, Simbang District, Maros Regency. The research design used was a randomized block design which was arranged in a factorial manner, where the first factor was the planting medium which consisted of 3 treatments and the second factor was liquid organic fertilizer from rice washing water which consisted of 4 treatments so that there were 12 combinations of repeated treatments. 3 times so that there are 36 experimental units. The results of the study gave the best growth in the sandy soil media treatment on plant height parameters, while the soil growing media gave the best growth on the number of leaves, number of petioles, number of stems per clump and plant fresh weight. Meanwhile, the application of liquid organic fertilizer from rice washing water and the interaction between the treatment of growing media and the application of liquid organic fertilizer from rice washing water had no significant effect on the growth of celery plants